Efficacy of cognitive therapy and behavior therapy for menopausal symptoms: a systematic review and meta-analysis. Issue 3 (11th February 2022) - Ye, Mengfei; Shou, Mengna; Zhang, Jian; Hu, Baiqi; Liu, Chunyan; Bi, Chenchen; Lv, Tingting; Luo, Fangyi; Zhang, Zeying; Liang, Shenglin; Feng, Hong; Qian, Chao; et al.
Abstract: Background: T long-term effects of cognitive therapy and behavior therapy (CTBT) for menopausal symptoms are unknown, and whether the effects are different between natural menopause and treatment-induced menopause are currently unclear. Therefore, we sought to conduct an accurate estimate of the efficacy of CTBT for menopausal symptoms. Methods: We conducted searches of Cochrane Library, EMBASE, PsycINFO, PubMed, and Web of Science databases for studies from 1 January 1977 to 1 November 2021. Randomized controlled trials (RCTs) comparing intervention groups to control groups for menopausal symptoms were included. Hedge's g was used as the standardized between-group effect size with a random-effects model. Results: We included 14 RCTs comprising 1618 patients with a mean sample size of 116. CTBT significantly outperformed control groups in terms of reducing hot flushes [ g = 0.39, 95% confidence interval (CI) 0.23–0.55, I 2 = 45], night sweats, depression ( g = 0.50, 95% CI 0.34–0.66, I 2 = 51), anxiety ( g = 0.38, 95% CI 0.23–0.54, I 2 = 49), fatigue, and quality of life. Egger's test indicated no publication bias. Conclusions: CTBT is an effective psychological treatment for menopausal symptoms, with predominantly small to moderate effects. The efficacy is sustained long-term, although it declines somewhat over time. The efficacy was stronger for natural menopause symptoms, such as vasomotor symptoms, than for treatment-induced menopause symptoms. These findings provide support for treatment guidelines recommending CTBT as a treatment option for menopausal symptoms.